Photonic Funnels: Subdiffraction Limited Photonic Funneling of Light (Advanced Optical Materials 24/2020). Issue 24 (17th December 2020) - Li, Kun; Simmons, Evan; Briggs, Andrew; Nordin, Leland; Xu, Jiaming; Podolskiy, Viktor; Wasserman, Daniel
Abstract : Efficient optical coupling between deep subwavelength and diffraction limited domains can open numerous applications in microscopy, spectroscopy, communications, and sensing. In article number 2001321, Viktor Podolskiy, Daniel Wasserman and co‐workers experimentally demonstrate and numerically investigate photonic funnels, a platform that enables such coupling. The funnels comprise hyperbolic metamaterial cores that support propagation of strongly confined modes and highly conductive cladding that prevents leakage of light through the structure's ides. The funnels are realized in the important mid‐infrared frequency range with a semiconductor‐based designer metal platform.